Strategi Ekonomi Kreatif dalam Meningkatkan Daya Saing Produk UMKM: Pengabdian - Arniwita; Febrina, Ilza; Rachmania, Dewi; Rahman, Kristanti; Sasmita, Djenni; Zulaecha, Hesty Erviani; Sudarmanto, Eko (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The Community Service activity themed "Creative Economy Strategies in Enhancing the Competitiveness of MSME Products" was conducted online via the Zoom platform on May 10, 2025. This initiative aimed to enhance participants’ understanding of the concepts and applications of the creative economy in MSME product development, to encourage ethics-based innovation, and to strengthen networking among members of the SSQ Community. The event was enthusiastically attended by more than 90 participants, comprising alumni of the Certified Business in Quran (CBsQ) and Certified Management in Quran (CMtQ) programs, as well as MSME practitioners and members of the general public. Dr. Arniwita, MM, from Universitas Muhammadiyah Jambi, served as the keynote speaker, delivering a presentation on strategies for product diversification, creative branding, digitalization, and inter-MSME collaboration. The outcomes of this activity indicated that participants gained new insights into the importance of innovation in enhancing competitiveness, were motivated to adopt creative economy concepts in their enterprises, and established a communication forum for business collaboration. This program is expected to serve as an initial step in building a creative, innovative, highly competitive, and sustainable MSME ecosystem at both national and international levels.